The effect of alpha-phenyl-N-tert-butyl nitrone on bioenergetic state in substantia nigra following flurothyl-induced status epilepticus in rats - Folbergrová, J; He, Q P; Li, P A; Smith, M L; Siesjö, B K (Neuroscience letters, 1999)
Status epilepticus (SE), i.e. ongoing seizures of more than 30 min duration, gives rise to bilateral pan-necrotic lesions of the substantia nigra, pars reticulata (SNPR). These are known to be preceded by an initial increase, followed by a depression of metabolic rate, and by failure of the bioenergetic state, suggesting mitochondrial dysfunction. We have previously shown that the spin trap alpha-phenyl-N-tert-butyl nitrone (PBN) prevents the lesions caused by 45 min of SE from occurring, in spite of ongoing seizure activity. In this article, we demonstrate that PBN, given 30 min before seizure induction, reduces or prevents the decrease in ATP concentration and adenylate energy charge, without significantly reducing the amount of lactate accumulated, or the decrease in intracellular pH (pHi). The results suggest that the spin trap nitrone preserves the structural and functional integrity of SNPR neurons by protecting the mitochondria against oxidative damage.
Keywords: Nitrogen Oxides; Flurothyl; konvulziva; oxidy dusíku; Cyclic N-Oxides; Convulsants; status epilepticus; krysa rodu Rattus; spinové značení; zvířata; Substantia Nigra; scavengery volných radikálů; potkani Wistar; Free Radical Scavengers; Energy Metabolism; energetický metabolismus; Rats, Wistar; Male; substantia nigra; flurothyl; Rats; cyklické N-oxidy; Animals; Status Epilepticus; mužské pohlaví; Spin Labels